Single-pixel reconstructive mid-infrared micro-spectrometer - Dong, Kaichen; Li, Jiachen; Tiancheng Zhang; Fangda Gu; Yuhang Cai; Niharika Gupta; Tang, Kechao; Ali Javey; Yao, Jie; Wu, Junqiao (Opt. Express, 2023)
Miniaturized spectrometers in the mid-infrared (MIR) are critical in developing next-generation portable electronics for advanced sensing and analysis. The bulky gratings or detector/filter arrays in conventional micro-spectrometers set a physical limitation to their miniaturization. In this work, we demonstrate a single-pixel MIR micro-spectrometer that reconstructs the sample transmission spectrum by a spectrally dispersed light source instead of spatially grated light beams. The spectrally tunable MIR light source is realized based on the thermal emissivity engineered via the metal-insulator phase transition of vanadium dioxide (VO2). We validate the performance by showing that the transmission spectrum of a magnesium fluoride (MgF2) sample can be computationally reconstructed from sensor responses at varied light source temperatures. With potentially minimum footprint due to the array-free design, our work opens the possibility where compact MIR spectrometers are integrated into portable electronic systems for versatile applications.
Keywords: Fourier transform infrared spectroscopy; Fourier transforms; Light beams; Light sources; Optical systems; Quantum cascade semiconductor lasers